2021
DOI: 10.1177/03635465211041763
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Midterm Outcomes of High-Level Athletes Versus Nonathletes Undergoing Primary Hip Arthroscopy: A Propensity-Matched Comparison With Minimum 5-Year Follow-up

Abstract: Background: High-level athletes (HLAs) have been shown to have better short-term outcomes than nonathletes (NAs) after hip arthroscopy. Purpose: (1) To report midterm outcomes of HLAs after primary hip arthroscopy and (2) to compare their results with a propensity-matched cohort of NA patients. Study Design: Cohort study; Level of evidence, 3. Methods: Data were prospectively collected and retrospectively reviewed between February 2008 and November 2015 for HLAs (professional, college, or high school) who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…The power analysis was calculated based on the expected mean difference and standard deviation of the mHHS, 8 and 10 points, respectively. 35 According to the power analysis, 17 hips in the basketball group and 51 hips in the cutting sports group were needed to minimize the possibility of type 2 errors.…”
Section: Methodsmentioning
confidence: 99%
“…The power analysis was calculated based on the expected mean difference and standard deviation of the mHHS, 8 and 10 points, respectively. 35 According to the power analysis, 17 hips in the basketball group and 51 hips in the cutting sports group were needed to minimize the possibility of type 2 errors.…”
Section: Methodsmentioning
confidence: 99%
“… 30 A more recent study confirmed the persistence of this trend, with 250% more procedures performed over a 4-year span from 2007 to 2011. 43 Contemporary literature has demonstrated a high rate of return to sport, 9 , 12 , 27 , 28 as well as significant improvements in pain, function, and patient satisfaction at short-, 2 , 11 , 26 , 37 mid-, 16 , 34 and long-term follow-up. 23 Studies evaluating postoperative biomechanical outcomes, however, have remained sparse.…”
mentioning
confidence: 99%
“…Previous literature has documented the differences between athletes and nonathletes undergoing primary hip arthroscopy at both minimum 2- and 5–year follow–up. 12,32 Clapp et al 12 established that at minimum 2–year follow–up, competitive athletes undergoing primary hip arthroscopy demonstrated higher rates of achieving the MCID for the HOS-SSS and higher postoperative HOS-SSS scores compared with nonathletes. As a result, athletes seem to represent a distinct population with higher demands than the general population undergoing hip arthroscopy, but the evidence on this topic continues to evolve.…”
Section: Discussionmentioning
confidence: 99%